PENGARUH PENJUALAN TERHADAP CURRENT RATIO, QUICK RATIO DAN CASH RATIO PADA PT. CAHAYA PRIMA SENTOSA (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2019)
The purpose of this study is to determine whether there is an effect of sales on the current ratio, quick ratio and cash ratio of the company's liquidity at PT. Cahaya Prima Sentosa. The type of data in this study is secondary data which is quantitative data in the form of nominal figures from the company studied in the form of financial reports of PT. Cahaya Prima Sentosa 2012-2016. Testing the hypothesis in this study using simple linear regression with t test and F test. Based on the results of research that has been done: That sales volume has a strong effect on Current Ratio, which means that sales have a strong effect on Current Ratio, Hypothesis testing using correlation analysis shows that sales volume has a strong effect on liquidity and Hypothesis testing using correlation analysis results show that sales have a strong effect on liquidity.